2017
DOI: 10.1002/stem.2575
|View full text |Cite|
|
Sign up to set email alerts
|

Concise Review: MSC-Derived Exosomes for Cell-Free Therapy

Abstract: Mesenchymal stem cell transplantation is undergoing extensive evaluation as a cellular therapy in human clinical trials. Because MSCs are easily isolated and amenable to culture expansion in vitro there is a natural desire to test MSCs in many diverse clinical indications. This is exemplified by the rapidly expanding literature base that includes many in vivo animal models. More recently, MSCderived extracellular vesicles (EVs), which include exosomes and microvesicles (MV), are being examined for their role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
1,046
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,333 publications
(1,116 citation statements)
references
References 103 publications
13
1,046
0
7
Order By: Relevance
“…Recent studies showed that extracellular vesicles (EVs)/exosomes alone contributed to the therapeutic effects of MSCs in multiple animal models, such as those for ischemic stroke [16,58,59], acute kidney injury [60] and traumatic brain injury [17]. Exosomes comprise one of the main subclasses of EVs and are considered the most promising therapeutic mediator of MSC function by altering the activity of target cells via horizontal transfer of mRNAs, microRNAs, and proteins [61]. Compared with factors in the absence of membrane packaging, exosomes are more stable and capable of targeting inflammatory sites due to their enhanced permeability and retention effects [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that extracellular vesicles (EVs)/exosomes alone contributed to the therapeutic effects of MSCs in multiple animal models, such as those for ischemic stroke [16,58,59], acute kidney injury [60] and traumatic brain injury [17]. Exosomes comprise one of the main subclasses of EVs and are considered the most promising therapeutic mediator of MSC function by altering the activity of target cells via horizontal transfer of mRNAs, microRNAs, and proteins [61]. Compared with factors in the absence of membrane packaging, exosomes are more stable and capable of targeting inflammatory sites due to their enhanced permeability and retention effects [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…As tonsillar tissues are discarded after surgery, the isolation of stem cells from these discarded tissues offers another valuable means of recycling human tissue for stem cell therapy [20,23]. In addition, the T-MSCs have MSC characteristics and are known to secrete various cytokines [27], growth factors [28], and exosomes [29] considered suitable for cell therapy. The T-MSCs show excellent immune modulation activity and no immunologic problems even when the T-MSCs were combined from three independent donors [23].…”
Section: Discussionmentioning
confidence: 99%
“…21 The discovery of MSC-derived exosomes that act in a paracrine/endocrine fashion is an important step toward cell-free MSC therapy. 22 MSCs and their exosomes are known to recognize tumors and metastases as wounds, migrate to them and integrate into the tumor stroma. Stoff-Khalili et al have shown that intravenous injection of human MSCs loaded with conditionally replicating adenoviruses targeted MDA-MB-231 mouse model of metastatic breast cancer in vivo.…”
Section: Discussionmentioning
confidence: 99%